Ruptured Deep Femoral Artery Aneurysm Confused with an Incarcerated Inguinal Hernia: a Case of an Elderly Patient - Nishimura, Kengo (Int J Angiol, 2019)
Deep femoral artery (DFA) aneurysms are rare. DFA is protected by the adductor canal, which may delay the diagnosis. Then, its early diagnosis may be difficult and it is possible to be misdiagnosis with incarcerated inguinal hernia, which occurs more often in elderly people. We report a very rare case of a treatment of an advanced elderly patient with an isolated ruptured DFA aneurysm that was preoperatively confused with an incarcerated inguinal hernia. A 97-year-old man was admitted to a neighboring hospital due to a painful mass of the right groin after transient consciousness loss and the patient was diagnosed with right incarcerated inguinal hernia by a nonenhanced computed tomography (CT). Although he was observed for 3 days, he suddenly lost consciousness again with a decrease in blood pressure. Thus, he was referred to our hospital due to the painful pulsatile inguinal mass after resuscitation from shock. As we diagnosed a ruptured DFA aneurysm by an enhanced CT, we emergently performed an excision of the aneurysm with revascularization of the right DFA. The postoperative course was uneventful without ischemic change of the lower leg.